Updated results of 100 patients on clinical features and therapeutic options in necrobiosis lipoidica in a retrospective multicentre study - Dissemond, Joachim; Schwede, Katharina; Seitz, Anna-Theresa; Al Ghazal, Philipp; Wollina, Uwe; Renner, Regina; Erfurt-Berge, Cornelia (European Journal of Dermatology, 2015)
Necrobiosis lipoidica (NL) is a rare granulomatous disorder of unknown aetiology which can manifest in ulcerative skin lesions and is widely recognised in association with diabetes. We evaluated in total 100 patients to improve knowledge about the epidemiology and clinical course of NL. Additionally we focused on treatment options according to evidence level and expert opinion.To examine the clinical features of patients with necrobiosis lipoidica and to give recommendations for topical and systemic treatment.This multicentre retrospective study covers data from 100 patients with the diagnosis of NL of the lower leg, treated during the period between 01/2006 and 06/2014. Data from 5 German dermatological centres with 23 men and 77 women with a median age of 52 years were evaluated. We also asked 15 dermatological experts for their opinions about ulceration, associated diseases and their preferences for treatment modalities of NL.Patients' ages ranged from 15 to 95 years (median age 52 years, mean age 49.8 years). NL was significantly more common in women (77%). Ulceration of the NL was observed in 33% of cases, in particular in male patients and in patients with concomitant diabetes mellitus. Thyroidal disorders were found in 15% of all cases.Our data confirm that female sex, middle age and endocrine disorders like diabetes mellitus or thyroid dysfunction are characteristics of patients suffering from NL. Existing therapeutic options were very variable and - according to the opinion of our experts - only a few highly effective.
EVALuna2:19576